The Higher You Think of Yourself, the Harder You Fall: Overconfidence as a Distinct, Mutable Predictor of Fake News Vulnerability - Secară, Eugen-Călin; Opre, Nicolae-Adrian (Studia Psychologica, 2025)
This study investigated whether memory overconfidence is predictive of fake news vulnerability when controlling for previously established predictors and whether it can be experimentally reduced (N = 395). Participants completed measures of reflexive and reflective open-minded thinking, rated news articles collected from untrustworthy sources and completed general knowledge and working memory tasks. Confidence was assessed after each trial. The control group received feedback on the time spent on the tasks, while the experimental group was informed about the number of incorrect answers and their average confidence level. Afterwards, both groups completed the rest of the general knowledge and working memory tasks, alongside the confidence assessment and then rated other fake news articles. While neither reflexive nor reflective open-minded thinking significantly predicted fake news vulnerability, memory overconfidence did. Overconfidence correcting feedback reduced overconfidence but not fake news vulnerability. These findings indicate that memory overconfidence is a robust, mutable predictor of fake news vulnerability and highlight the need for more in-depth behavioral research.